CARTESIAN IDEALISM AND AMAZON ISSUES - Barbosa, Cloves; Wilson Tafner Junior , Armando (Revista Gênero e Interdisciplinaridade, 2025)
This papar intorduce the Descartes’ idealism with their locus into the epistemologies with the general and the region. The Descartes’ belief to be determine your theorization about Gad conception. The idealism’ Descartes’ philosophical has that goal.